2011
DOI: 10.1063/1.3658047
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation on polymer translocation in crowded environment

Abstract: The effect of crowded environment with static obstacles on the translocation of a three-dimensional self-avoiding polymer through a small pore is studied using dynamic Monte Carlo simulation. The translocation time τ is dependent on polymer-obstacle interaction and obstacle concentration. The influence of obstacles on the polymer translocation is explained qualitatively by the free energy landscape. There exists a special polymer-obstacle interaction at which the translocation time is roughly independent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 52 publications
(87 reference statements)
6
42
0
Order By: Relevance
“…In addition to the EV effect of NPs, polymer-NP attraction would also change the free-energy landscape of polymer translocation, and thus it affects the translocation property of polymers [40][41][42][43]. Both the dynamic Monte Carlo (MC) simulation and the Langevin dynamics (LD) simulation showed that the polymer-NP attraction could obviously change the translocation time of polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the EV effect of NPs, polymer-NP attraction would also change the free-energy landscape of polymer translocation, and thus it affects the translocation property of polymers [40][41][42][43]. Both the dynamic Monte Carlo (MC) simulation and the Langevin dynamics (LD) simulation showed that the polymer-NP attraction could obviously change the translocation time of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Both the dynamic Monte Carlo (MC) simulation and the Langevin dynamics (LD) simulation showed that the polymer-NP attraction could obviously change the translocation time of polymers. The attractive NPs at the trans side could draw the polymer through the pore by lowering the energy, and thus decrease the translocation time [40]. However, the diffusion rate of polymers was slowed down at strong polymer-NP attraction because the polymers were adsorbed on NPs, thus the translocation time was significantly increased at strong polymer-NP attraction.…”
Section: Introductionmentioning
confidence: 99%
“…In the first regime R G0 > D > σ f , normal diffusion < Δr 2 > ∝t is always observed at long time scale, even at large ε fp . Such behavior is different from the subnormal diffusion of a polymer in a crowding environment with random fillers (12). At strong polymer-filler interactions, although the diffusion of the polymer is slow, the normal diffusion survives at a long time scale after In the second regime D > R G0~σf , normal diffusion < Δr 2 > ∝t is only observed at small ε fp before the adsorption.…”
Section: Resultsmentioning
confidence: 97%
“…Experiments found that the thermal and mechanical properties of polymethyl methacrylate/carbon nanofibers were significantly enhanced when compared to polymethyl methacrylate with no carbon nanofibers (11). Moreover, it was found that a normal diffusion of polymer in dilute solution will change to a sub-diffusion in media with random distributed fillers (12). In addition, the translocation of the polymer was dependent on the properties of fillers (12,13).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation